Florida 4-H Air Rifle & Smallbore Rifle Record Book - Julie Pigott Dillard; Gerald Culen (EDIS)
The purpose of this 13-page Florida 4-H Air Rifle/Smallbore Rifle book is to help 4-H members document their growth, development, and progress in the titular activities. Written by Julie P. Dillard and Gerald Culen and published by the UF/IFAS 4-H Youth Development Department, August 2018. https://edis.ifas.ufl.edu/4h391